Analisis Pengaruh Situasi Kerja, Kepuasan Kerja dan Motivasi Kerja terhadap Kinerja - Syahyono . (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2016)
The background of this research is to collect data and information on employee perceptions of workplace situations , job satisfaction and motivation are running at this time and its relationship with the employee's performance . The purpose of this study presented is to know Influence Analysis : work situation , work job satisfaction , motivation and employee performance environment Pt . Rays Griya Utama . This research was conducted in Pt . Rays Griya Utama . Data were collected by using a questionnaire , and sampling this study as many as 65 employees of probability sampling . The data analysis method used is multiple regression test , F test , and the coefficient of determination (R ²) The results showed that: 1). Partially Employment Situation t test variable (X1) effect on the performance of employees at PT. Rays Griya Utama. It is known from p-value less than 0.05. 2). Partially Job Satisfaction variable t test (X2) effect on the performance of employees at PT. Rays Griya Utama. It is known from p-value less than 0.05. 3). Partially Work motivation variable t test (X3) does not affect the performance of employees at PT. Rays Griya Utama. It is known from p-value greater than 0.05. Based on the result showed that motivation in PT. Rays Top Griya need not be held because the employees are self-motivated, and to increase the motivation of employees need their money incentives for high achievers. 4). Simultaneously (F test) Situation variable Work, Job Satisfaction, and Work Motivation has a significant influence on employee performance in PT. Rays Griya Utama. It is known from p-value less than 0.05